IMPLEMENTASI NILAI AJARAN TAT TWAM ASI DALAM MEMBENTUK KARAKTER MULIA SISWA DI SMP NEGERI 1 SINGARAJA - Komang Dedi Juniarta; I Gede Agung Jaya Suryawan; I Ketut Pasek Gunawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Cultivating noble character in students has emerged as a critical concern in the modern educational landscape, particularly as technological progress and complex social dynamics increasingly pose moral challenges to the younger generation. Within the Hindu philosophical tradition, the teaching of Tat Twam Asi which conveys the meaning that every human being shares a fundamental spiritual unity holds significant relevance for character-based education. This teaching encourages individuals to regard others as reflections of themselves, thereby nurturing values of empathy, mutual respect, and social responsibility. This study aims to examine the challenges encountered, the strategies employed, and the educational outcomes resulting from the application of Tat Twam Asi teachings in forming noble character among students at SMP Negeri 1 Singaraja. A qualitative research methodology with a phenomenological approach was adopted to explore the lived experiences of participants. Data were gathered from the school principal, Hindu Religious Education teachers, guidance and counseling teachers, homeroom teachers, and students through structured observation, in-depth interviews, and documentary review. The data were subsequently analyzed using the Miles and Huberman interactive model encompassing data condensation, data presentation, and conclusion verification. Findings indicate that the implementation process still confronts internal barriers, including students' adolescent egocentrism and insufficient internalization of empathy, honesty, and responsibility. External barriers arise from unsupportive family environments, negative peer influences, and the pervasive impact of social media. Implementation strategies involve integrating Tat Twam Asi values through Hindu Religious Education lessons, exemplary conduct by educators, consistent positive behavioral habituation, religious activities, and socially constructive school interactions. The resulting implications include observable improvements in students' peaceful, communicative, honest, and responsible character traits. This study affirms that Tat Twam Asi teachings serve as a meaningful foundation for strengthening character education within the school community.